Utilisation of co-testing (human papillomavirus DNA testing and cervical cytology) after treatment of CIN: a survey of GPs’ awareness and knowledge - Munro, A.; Codde, J.; Semmens, James; Leung, Y.; Spilsbury, Katrina; Williams, Vincent; Steel, N.; Cohen, P.; Pavicic, H.; Westoby, V.; O'Leary, Peter (The Royal Australian College of General Practitioners, 2015)
Background - Patients have an increased risk of persistent/recurrent cervical disease if they received treatment for a high-grade squamous intraepithelial lesion (HSIL). Consequently, understanding whether co-testing (human papillomavirus [HPV] DNA testing and cervical cytology) is fully utilised by general practitioners (GPs) is paramount. Methods - After consultation with key stakeholders, an anonymous, self-completion questionnaire was developed and disseminated to GPs who had provided cervical cytology. Results - Responses were received from 745 GPs (30.9% response rate). A significant number (34.3%) of GPs were unaware of the use of co-testing (HPV DNA testing and cervical cytology) for the management of patients after HSIL treatment. Additionally, the majority of GPs reported they did not ‘always’ receive a clear follow-up plan for patients after treatment of an HSIL. Discussion - GPs require further support and education to ensure successful adoption of co-testing (HPV DNA testing and cervical cytology), specifically, for patients treated for an HSIL.